The Influence of Online Store Beliefs towards Impulse Buying (Study on Elevania.co.id) - Citra Kusuma Dewi; Despri Lolita br Sinuraya (Bina Nusantara University, 2015)
The rapid development of information technology brings a great impact to all aspects, including the development of business and marketing. The rapid growth of internet user makes online business becomes a potential market. One of the factors that determine the success of an online business is consumer beliefs to an online store. The purpose of this study is to determine the influence of online stores beliefs towards impulse buying on elevenia consumers. This study was conducted on elevenia consumers who have shopped at elevenia.co.id. Sample size of 100 people with purposive sampling method. Data was collected through questionnaires using a 5 point Likert scale to measure 11 indicators. The analysis technique is multiple linear regression. The research found that the online store beliefs variable consist of functional convenience beliefs and representation delight, simultaneously influence impulse buying on elevenia consumers.While in partial functional convenience beliefs variable have no influence towards impulse buying on elevenia consumers.